Definitive External Fixation for Anterior Stabilization of Combat-related Pelvic Ring Injuries, With or Without Sacroiliac Fixation. Issue 4 (April 2020) - Hoyt, Benjamin W.; Lundy, Alexander E.; Purcell, Richard L.; Harrington, Colin J.; Gordon, Wade T.
Abstract: Background: Combat-related pelvic ring injuries frequently lead to placement of a temporizing external fixation device for early resuscitation and transport. These injuries are commonly complicated by concomitant polytrauma and extensive soft-tissue injuries, which may preclude early internal fixation and lead to prolonged use of external fixation. To date, few studies have reported on the outcomes of definitive external fixation for combat-related pelvic ring injuries. Questions/purposes: (1) In patients treated with definitive external fixation after combat-related pelvic ring injuries, how often is the quality of reduction within radiographically acceptable parameters at the end of treatment? (2) What proportion of patients demonstrate local heterotopic ossification after these injuries? (3) What patient- and treatment-related factors are associated with increased complications and pain? Methods: We retrospectively studied all patients with pelvic ring injuries treated at a tertiary military referral center from January 2003 to December 2012. In total, 114 patients were identified, 55 of whom maintained an external fixation frame throughout their treatment. During that time, the general indications for definitive external fixation were an open, contaminated pelvic ring injury with a high risk of infection or open urologic injury; confluent abdominal, perineal, and thigh wounds; or comminution of the pubic ramus that would necessitate plate fixation extending up the anterior column in patients with open abdomen or exposure-compromising abdominal wounds. Posterior fixation, either sacroiliac or lumbopelvic, was applied in patients with sacroiliac instability. Of the 55 patients with pelvic ring injuries treated with definitive external fixation (27 open and 28 closed), four underwent hemipelvectomy and construct removal for massive ascending infections and four were lost to follow-up, leaving 47 patients (85%) who were available at a minimum follow-up of 12 months (median 29 months, interquartile range 17-43 months). All 47 patients underwent serial imaging to assess their injury and reduction during treatment. External fixators were typically removed after 12 weeks, except in patients in whom pin-site irritation or infection prompted earlier removal, and all were confirmed to be grossly stable during an examination under anesthesia. Clinical union was defined as the absence of radiographically present fracture lines and stable examination findings under anesthesia when the external fixator was removed. Data on demographics, injury pattern, associated injuries, revision procedures, complications, and final functional outcomes including ambulation status, sexual function, and pain were collected. Pelvic radiographs were reviewed for the initial injury pattern, type of pelvic fixation construct, residual displacement after removal of the frame, and evidence of formation of heterotopic ossification in the pelvis or bilateral hips. Pelvic displacement and diastasis were determined by digital caliper measurement on plain images; malunion was defined as anterior diastasis of the pelvis or vertical incongruity of the hemipelvis greater than 10 mm. Results: Radiographic malunion after construct removal occurred in eight of 24 patients with open injuries and in five of 23 patients with closed injuries. Heterotopic ossification developed in the pelvis or hips of all 24 patients with open injuries and in two of the 23 patients with closed injuries. In patients with open pelvic ring injuries, concomitant acetabular fractures were associated with pelvic pain at the final follow-up examination (risk ratio 1.9; 95% confidence interval, 1.0-3.5; p = 0.017). No treatment factor resulted in superior functional outcomes. In the closed-injury group, concomitant lower-extremity amputation was associated with improved radiographic final reduction (RR 0.4; 95% CI, 0.2-0.7; p = 0.02). There was no association between radiographic malunion and increased pain (RR 1.9; 95% CI, 0.5-7.0; p = 0.54 for the open group; RR 0.8; 95% CI, 0.7-1.0; p = 0.86 for the closed group). Conclusion: In this series of patients with severe combat-related pelvic ring injuries who were treated anteriorly with definitive external fixation because of a severe soft-tissue injury, high infection risk, or unacceptable physiologic cost of internal fixation, malunion and chronic pelvic pain were less common than previously observed. Prior studies primarily differ in their lack of sacroiliac or lumbopelvic stabilization for posteriorly unstable fracture patterns, likely accounting for much of these differences. There may have been important between-study differences such as extremely severe injuries, concomitant injuries, and study population. Our study also differs because we specifically analyzed a large cohort of patients who sustained open pelvic ring injuries. Future studies should prospectively investigate the ideal construct type and pin material, optimize the length of treatment and assessment of healing, and improve radiographic measures to predict long-term functional outcomes. Level of Evidence: Level IV, therapeutic study.